Effect of cytoskeleton on ice crystal growth in cells during freezing. Issue 1 (1st January 2018) - Xie, Yanqi; Zhu, Kai; Wang, Yabo; Chen, Tong
ABSTRACT: The factors affecting intracellular ice formation (IIF) and growth is essential to the mechanistic understanding of cellular damage through freezing. In the aid of high speed and high-resolution cryo-imaging technology, the broad bean intracellular ice formation and growth processes were successfully captured during freezing. Cytochalasin B（CB）was used to solubilize the cytoskeleton. Images of IIF were compared between cells with and without cytoskeleton. The behavior of intracellular ice crystal formation in plant tissues with or without CB was evaluated using changes of cell areas, the probability of crystallization, and growing rate of intracellular ice crystal. Moreover, light intensity figures were used to determine cell damage. This study showed that the cytoskeleton was involved in ice crystal nucleation mechanism during freezing responses of the plant cells.